The persistence of attentional set and its implications for top-down control - Thompson, Catherine (2009)
A top-down attentional set allows selective processing of the most informative aspects of a scene by biasing attention towards task-relevant stimuli and away from task-irrelevant stimuli on the basis of task demands. The work in this thesis explored the characteristics of the attentional set and top-down control by measuring the persistence of a set. That is, the carry-over of a set from a task in which it is appropriate to a subsequent task in which it is inappropriate. Twelve experiments were completed, employing three different methodologies in order to provide converging evidence for the persistence of attentional set. The first method was a rapid serial visual presentation task, the second was a change detection task that was preceded by a visual search task, and the third was a visual search of natural scenes following an unrelated search through letter strings. All three methodologies provided strong evidence for the carry-over effect, whereby the allocation of attention in a second task was influenced by the top-down settings from the first task. This shows that an attentional set is not established solely based on current task demands but is also influenced by previous experience. Carry-over appears to be contingent upon the level of control invested in the task; too much control over the initial top-down set will enhance carry-over, but a high level of control in the second task will attenuate carry-over. In addition, a lack of executive control over the set will also lead to carry-over when the set is highly practiced because task performance will not be monitored, and a change in task demands will not be accompanied by a change in attentional set. Carry-over provided evidence for three different types of attentional set; a location-based set, a feature-based set, and a feature-value-based set. It also indicated that the attentional orienting system can be configured at more than one level according to the task demands, implying that top-down control is more flexible than previously suggested. The work ultimately led to the development of a general model of attentional set (G-MAS) which attempts to explain the current results and account for pertinent findings from the literature.